Zero and Nonzero Mass Flux Effects of Bioconvective Viscoelastic Nanofluid over a 3D Riga Surface with the Swimming of Gyrotactic Microorganisms. (16th July 2021) - Karthik, T. S.; Loganathan, K.; Shankar, A. N.; Carmichael, M. Jemimah; Mohan, Anand; Kaabar, Mohammed K. A.; Kayikci, Safak
Abstract : This work addresses 3D bioconvective viscoelastic nanofluid flow across a heated Riga surface with nonlinear radiation, swimming microorganisms, and nanoparticles. The nanoparticles are tested with zero (passive) and nonzero (active) mass flux states along with the effect of thermophoresis and Brownian motion. The physical system is visualized via high linearity PDE systems and nondimensionalized to high linearity ordinary differential systems. The converted ordinary differential systems are solved with the aid of the homotopy analytic method (HAM). Several valuable and appropriate characteristics of related profiles are presented graphically and discussed in detail. Results of interest such as the modified Hartmann number, mixed convection parameter, bioconvection Rayleigh number, and Brownian motion parameter are discussed in terms of various profiles. The numerical coding is validated with earlier reports, and excellent agreement is observed. The microorganisms are utilized to improve the thermal conductivity of nanofluid, and this mechanism has more utilization in the oil refinery process.